“ Le Vallier Ouest ”à Mainvilliers (Eure-et-Loir, 28) : indices d’un habitat du Néolithique ancien (Villeneuve-Saint-Germain) entre Loire et Seine - Frédéric Dupont; François Fouriaux; Nicolas Garmond; Colas Gueret; Roland Irribarria; Apolline Louis (Revue Archéologique du Centre de la France)
Despite the delicate context owing to the nature of the substrate and to more recent structures, the excavation site of the Vallier Ouest (Mainvilliers, Eure-et-Loir, France) revealed indications of the presence of a settlement dated from the ancient Neolithic. These indications are, firstly, the material remains (pottery and lithic) attributable evenly to the end of Villeneuve-Saint-Germain and the other few hollow structures indicating the location of buildings or areas of activity. If the lithic corpus is original in its origin and the proportion of blades, these elements as a whole and traceological study tell of an occupation of a domestic nature that cannot be completely understood because of the poor preservation of the site. This site however still offers new keys to the understanding the Neolithic expansion between the Loire and Seine.